Electrochemical generation of a molecular heterojunction. A new Zn-Porphyrin-Fullerene C60 Polymeric Film. (1st June 2017) - Solis, Claudia; Ballatore, M. Belén; Suarez, María B.; Milanesio, María Elisa; Durantini, Edgardo N.; Santo, Marisa; Dittrich, Thomas; Otero, Luis; Gervaldo, Miguel
Graphical abstract: Highlights: A porphyrin and a porphyrin-C60 dyad are electropolymerized on Pt and ITO. A double cable polymeric structure is proposed for the porphyrin-C60 dyad. Photovoltage spectra fully match the absorption spectra of the polymeric films. Photoinduced charge separation and charge migration are observed in both films. Transitory photovoltage half-life time is longer for the polymer dyad. Abstract: The design and electrosynthesis of electroactive and photoelectroactive polymeric organic thin films holding Zn(II)-porphyrin and Zn(II)-porphyrin-C60 dyad are reported. The presence of carbazole substituents in the meso positions of the tetrapyrolic macrocycle allows the formation of conducting polymers by coupling of electrogenerated carbazole radical cations. Due to the fact that both donor and acceptor units in the monomer dyad are covalently bonded, a polymeric heterojunction can be formed in just one single step. The ITO/organic polymer electrodes were studied by cyclic voltammetry, UV-visible absorption spectroscopy and spectroelectrochemistry, showing that the porphyrin building blocks were not altered during the polymerization process and that they retained their light harvesting capacity and electrochemical characteristics. Upon illumination of the polymeric films, photoinduced charge separation and charge migration occur. The photovoltage spectra followed very well the absorption spectra of the organic materials, and in ITO/Zn-porphyrin-C60 electrodes, the signal amplitude and transitory photovoltage half-life time are larger than those observed for Zn-porphyrin polymer. Thus, a "double cable" polymeric structure is proposed for the material with the presence of the strong electron acceptor C60 fullerene, the hole transport porphyrin and dicarbazole moieties, making the material a potential building block for applications in the design and construction of organic optoelectronic devices.